ANALISIS PENGGUNAAN MEDIA SOSIAL BERBASIS TIKTOK TERHADAP PERILAKU BELAJAR SISWA (STUDI KASUS DI MI FAJAR SIDDIQ PALEMBANG) - Dwi Kartika, Anita; Boty, Middya; Tasya Jadidah, Ines (STKIP Subang, 2026)
This study aims to analyze Tiktok social media usage and its impact on the learning behavior of third-grade students at MI Fajar Siddiq Palembang. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The results showed that high-intensity Tiktok use, averaging more than 2-3 hours per day, significantly impacted students' self-efficacy, focus, and academic ethics. Although it can trigger academic procrastination and decreased attention span, Tiktok also offers potential as a creative learning tool if integrated into the Merdeka Curriculum framework. Effective digital literacy guidance from teachers and parents is crucial to balancing entertainment consumption with academic responsibilities.